IHAB HASSAN POSTMODERNISM’S INDETERMINACY AND IRONY:LAURA BROWN’S INNER CONFLICT IN THE HOURS - Rina Wahyu Setyaningrum (University of Muhammadiyah Malang, 2020)
Virginia Woolf is one of the modernist writers who write Mrs. Dalloway for which Michael Cunningham has taken Virginia’s life story into his novel, The Hours that characterized Laura Brown who reads Mrs. Dalloway. Cunningham’s literary work which foregrounds the uncertainty of sexual orientation, confusion, and difficulty of identity is suitable with postmodernism’s conventions and is valid in both Woolf's and Cunningham's novels. There have been studies conducted by the scholars in terms of various technical aspects, such as narrative, design, and structure. The other topics comprise the equivalence of characters, the parallelism of scenes, and the borrowing of themes and symbolism, in order to demonstrate the effects of the adaptation process. This paper focuses on Laura Brown’s inner conflicts which are connected to postmodernism features. From the quotations in the novel, this paper showcases the novel’s analysis based on Ihab Hassan’s theory of postmodernism’s indeterminacy and irony. It is found that Laura Brown’s inner conflicts are shown from her efforts of being a good wife for Dan. She is trying hard to answer her own question whether or not she loves her husband. Ironically, the perfect status of being a wife of a soldier who takes part in winning the World War II, a woman with a perfect family, as well as a woman living a good life, do not make her happy. Mrs. Dalloway has inspired her to find her true happiness, her former self that has disappeared.